Subnational malaria burden in Sindh, Pakistan: over a decade of evidence for tailored strategies - Nelofer Baig; Zakir Ali; Muhammad Ahmed; Wafa Zehra Jamal; Saqib Ur Rehman; Zafar Ahmed; Riaz Hussain Rahoojo; Javed Ali Jagirani; Bilal Ahmed Usmani; Zafar Fatmi (Malaria Journal)
Abstract Background Accurate estimates of malaria burden are crucial for allocating resources and designing effective control strategies. However, global reports often underestimate the burden in low- and middle-income countries, especially beyond the African region. This study addresses this gap by providing a longitudinal time-series analysis of malaria burden and spatio-temporal distribution in Sindh province, Pakistan. Methods Monthly suspected malaria cases reported from 1088 primary healthcare facilities managed by the PPHI-Sindh across 23 districts of Sindh Province (excluding seven districts of Karachi), Pakistan, were analysed over a 13-year period (2012–2024). Malaria incidence was determined by dividing total malaria cases by each health facility's catchment area population. Population-weighted estimates of malaria cases were calculated to account for variations in population size across districts. Yearly time-trend (with 95% CI), seasonal variation by month (with 95% CI), and a treemap illustrating the distribution of malaria burden across districts in Sindh. Results An incidence of 92 per 1000 people per annum of suspected malaria cases was reported at primary public healthcare facilities. Pooled estimates of 16.7 million cases occurred during a 13-year period, about 1.28 million cases annually. Marked heterogeneity observed in malaria burden across districts. Malaria positivity rate was 12.3%. Six districts (Khairpur, Sanghar, Naushero Feroze, Badin, Mirpurkhas, and Larkana) carried over 53% burden of malaria in Sindh. A distinct seasonal pattern with peak coinciding with the wet season and post-monsoon period was observed. Since the 2022 floods in Sindh, the malaria incidence has doubled, and it is persisting in the province. Conclusions The study highlights the substantial malaria burden with wet seasons and post-monsoon peaks in Sindh and identified few high-burden districts. The impact of 2022 flood seems to have persisted to 2024 and onwards, which needs immediate attention. Identification of high-burden districts could help tailor malaria control strategies. Also, the underestimation by global reports emphasizes the need for country-level and subnational analyses for informed decision-making. By addressing these gaps and refining burden estimates, Pakistan can develop more targeted strategies towards malaria control.